2003
DOI: 10.1101/gr.1119703
|View full text |Cite
|
Sign up to set email alerts
|

Targeting a Complex Transcriptome: The Construction of the Mouse Full-Length cDNA Encyclopedia

Abstract: We report the construction of the mouse full-length cDNA encyclopedia, the most extensive view of a complex transcriptome, on the basis of preparing and sequencing 246 libraries. Before cloning, cDNAs were enriched in full-length by Cap-Trapper, and in most cases, aggressively subtracted/normalized. We have produced 1,442,236 successful 3Ј-end sequences clustered into 171,144 groups, from which 60,770 clones were fully sequenced cDNAs Cold Spring Harbor Laboratory Press on May 10, 2018 -Published by genome.cs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
132
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 156 publications
(134 citation statements)
references
References 68 publications
2
132
0
Order By: Relevance
“…Making and sequencing subtracted cDNA libraries allows one to detect possible changes in mRNA-expression between two defined groups (25,33). In our libraries we found 800 unique cDNA-clones that appeared to differ between placental samples from women with PE and samples from healthy pregnant women.…”
Section: Discussionmentioning
confidence: 86%
“…Making and sequencing subtracted cDNA libraries allows one to detect possible changes in mRNA-expression between two defined groups (25,33). In our libraries we found 800 unique cDNA-clones that appeared to differ between placental samples from women with PE and samples from healthy pregnant women.…”
Section: Discussionmentioning
confidence: 86%
“…cDNAs were primarily obtained from cDNA libraries with~20,000 clones being analyzed Pompeia et al 2004), where approximately 2000 transcripts were identified only in the inner ear and likely representing rare to low-frequency inner ear transcripts. These unique ESTs represent 2Y3% of the current mouse transcriptome encyclopedia (Okazaki et al 2002;Carninci et al 2003) and are not currently represented by any commercial microarray chip. This microarray increases our chances of finding new or novel genes involved in hearing or in development of the ear.…”
Section: Discussionmentioning
confidence: 99%
“…The in situ probes used were against Hes1, Hes5, Notch2 (Akazawa et al, 1992), Mash1 (Carninci et al, 2003), Notch1 (a gift from Dr Andy Groves, Baylor College of Medicine, Houston, TX, USA), Nkx2.1 (a gift from Dr Lori Sussel, Columbia University, New York, NY, USA), Rax (a gift from Dr Seth Blackshaw, Johns Hopkins University, Baltimore, MD, USA) , Pomc (a gift from Dr Malcom Low, University of Michigan, Ann Arbor, MI, USA) (Japón et al, 1994), Ghrh (a gift from Dr Paul Le Tissier, MRC NIMR, London, UK) (Balthasar et al, 2003;Le Tissier et al, 2005). Probes were linearized and transcribed with polymerase in the presence of digoxigenin-labeled nucleotides.…”
Section: Histology Immunohistochemistry and In Situ Hybridizationmentioning
confidence: 99%